Legal foundations of social insurance in reducing occupational accident risks in the Republic of Kazakhstan - Baiterekova, К.Б.; Smatlayev, Б.М.; Ogurlu , Юджель (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article examines the processes of updating and adapting the legislation of the Republic of Kazakhstan in the field of mandatory social insurance against occupational accidents. The study focuses on two key aspects: the need to harmonize insurance regulations within the framework of the Eurasian Economic Union (EAEU) and the implementation of the standards of the International Labour Organization (ILO). The authors analyzed the main directions of modernization of the national social insurance system, which are linked to the development of the EAEU’s unified financial market and the necessity of introducing a proactive approach to managing occupational risks. It was found that the current insurance model has several limitations, including the absence of a preventive function and low efficiency of institutional structures, which operate primarily for commercial purposes rather than achieving socially significant outcomes. During the study, legal contradictions and terminological inconsistencies in the regulatory acts of the Republic of Kazakhstan governing occupational accident insurance were identified. Special attention was paid to comparing national legislation with ILO standards and examining the legal foundations for creating a unified insurance space within the EAEU. The scientific novelty and practical significance of the article lie in proposing a comprehensive approach to improving insurance legislation, which takes into account the balance of interests of the participants in insurance relations under conditions of Eurasian integration and the necessity of implementing the three key functions of insurance programs - compensatory, rehabilitative, and preventive. The study presents specific legal and organizational measures for harmonizing the regulatory framework, aimed at aligning Kazakhstan’s international obligations with its national priorities in social protection.